Checklist and Assessment of Pteridophytes in Amai Manabilang, Lanao Del Sur, Philippines - Bada, Jay Ann L.; Bierneza, David John D.; Coritico, Fulgent P.; Amoroso, Victor B. (Journal of Tropical Biology & Conservation (JTBC), 2023)
The species of ferns and lycophytes in Municipality of Amai Manabilang are documented here in a checklist, along with information on their morphological characteristics, and conservation status. A series of field surveys in two barangays in Amai Manabilang determined the lycophytes and ferns, namely Frankfort and Sumugot. A total of 56 species were recorded, belonging to 18 families and 36 genera. Of these species, 50 are ferns and 6 are lycophytes. The highest number of species was observed in Sumugot (42 species) followed by Frankfort (26 species). Thirty-one species are terrestrial, 19 are epiphytes, 1 tree fern and 5 species have more than one growth form. The number of species is approximately about 5% and 9% of the total number of pteridophytes species in the Philippines and Mindanao, respectively.